Translation, Systems and Research: The Contribution of Polysystem Studies to Translation Studies - Lambert, José (TTR)

(untitled) (Association canadienne de traductologie, 1995)
AbstractTranslation, Systems and Research: The Contribution of Polysystem Studies to Translation Studies — The aim of this article is not at all to examine Polysystems theory nor Polysystems research as such, but rather to discuss the impact Polysystems research has had in the development of a new discipline, i.e. Translation Studies. The ambiguous position of PS research within Translation Studies is due to its interdisciplinary claims and, on the other hand, to the necessity to work in a real world of disciplines where institutionalization is inevitable and even needed. The starting point of PS theory is not translation at all, but rather the dynamic functions fulfilled by translation within (inevitably) heterogeneous cultures and societies. On the basis of such hypotheses about culture(s) a rich panorama of new questions for research on translation has been worked out, as well as methodological models, and individual and collective descriptive research has been started in many countries on many cultural situations. Hence it may be accepted that descriptive research on translation would hardly have existed without the programmatic PS contribution and that the establishment of Translation Studies as an academic discipline is greatly indebted to PS. The gradual extension through various countries and disciplines (film studies, media studies, social organization, etc.) has favoured combinations with other approaches while making less clear the specific profile of the PS approach. It may be said that PS has served research as such, much more than its own sake, but wasn't this exactly the goal it wanted to achieve?